Expression and Correlation of Complement C3 and C4 in Serum and Maternal-Fetal Interface in Patients with Unexplained Recurrent Spontaneous Abortion: A Prospective Cohort Study - Zhengxin Zhou; Huixia Xie; Miao Liu; Ruopeng Li; Wenjing Jiang; Yan Zheng; Qun Lv (Clinical and Experimental Obstetrics & Gynecology, 2023)
Background: In this study, we sought to detect the expression of complement C3 and C4 in serum and maternal-fetal interface in patients with unexplained recurrent spontaneous abortion, and analyze their correlation, in order to explore the clinical significance and role of C3 and C4 in unexplained recurrent spontaneous abortion. Methods: In a prospective cohort study, products of conception of 20 women who underwent curettage due to unexplained recurrent spontaneous abortion in the Department of Obstetrics and Gynecology at the Sichuan Provincial People’s Hospital from December 2021 to December 2022 were chosen as the case group, and 23 healthy early-pregnancy women who underwent elective abortion due to personal reasons during the same period were chosen as the control group. Serum samples before curettage and decidual tissues samples after curettage were collected. C3 and C4 levels in serum samples were detected by immunoturbidimetry, and semi-quantitative scoring analysis was performed after immunohistochemical staining of decidual tissues samples. The correlation between C3 and C4 in serum and decidual tissues was analyzed. Results: The levels of C3 and C4 in serum and decidual tissues in the case group were significantly higher than those in the control group, and the differences were statistically significant (p < 0.05). There was a positive correlation between C3 and C4 in serum in the case group (r = 0.481, p < 0.05). There was no significant correlation between C3 and C4 in decidual tissues in the case group (p > 0.05). There was no significant correlation between C3 in serum and C3 in decidual tissues, nor between C4 in serum and C4 in decidual tissues in the case group (p > 0.05). Conclusions: The levels of C3 and C4 in serum and decidual tissues in the case group were higher than those in the healthy, normal early pregnancy women. This implies that elevated levels of activated C3 and C4 may be related to the pathogenesis of unexplained recurrent miscarriage. C3 and C4 can be used as early diagnostic criteria for recurrent miscarriage. There is a positive correlation between C3 in serum and C4 in serum in the case group, indicating that different pathways of complement activation may be involved in the pathogenic process of unexplained recurrent miscarriage.